1986
DOI: 10.1073/pnas.83.21.8333
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of 3'-azido-3'-deoxythymidine and selective interaction of the 5'-triphosphate with human immunodeficiency virus reverse transcriptase.

Abstract: The thymidine analog 3'-azido-3'-deoxythymidine (BW A509U, azidothymidine) can inhibit human immunodeficiency virus (HIV) replication effectively in the 50-500 nM range [Mitsuya, H., Weinhold, K. J., Furman, P. A., St. Clair, M. H., Nusinoff-Lehrman, S., Gallo, R. C., Bolognesi, D., Barry, D. W. & Broder, S. (1985) Proc. Naul. Acad. Sci. USA 82,[7096][7097][7098][7099][7100]. In contrast, inhibition of the growth of uninfected human fibroblasts and lymphocytes has been observed only at concentrations above 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
752
4
7

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,234 publications
(783 citation statements)
references
References 17 publications
(9 reference statements)
20
752
4
7
Order By: Relevance
“…NRTIs currently approved are zidovudine (AZT), didanosine (ddI), zalcitabine (ddC), lamivudine (3TC), stavudine (d4T), and abacavir (ABC). All of these compounds act in a similar way, as chain terminators of the RT reaction after phosphorylation by intracellular kinases (Furman et al 1986). NNRTIs in use are delavirdine (DLV), efavirenz (EFV) and nevirapine (NVP).…”
mentioning
confidence: 99%
“…NRTIs currently approved are zidovudine (AZT), didanosine (ddI), zalcitabine (ddC), lamivudine (3TC), stavudine (d4T), and abacavir (ABC). All of these compounds act in a similar way, as chain terminators of the RT reaction after phosphorylation by intracellular kinases (Furman et al 1986). NNRTIs in use are delavirdine (DLV), efavirenz (EFV) and nevirapine (NVP).…”
mentioning
confidence: 99%
“…Antiviral AZT efficacy depends on its initial transformation to AZT monophosphate (AZT-MP) by cellular thymidine kinase (TK), followed by further phosphorylation steps to AZT diphosphate and AZT triphosphate (AZT-TP), catalyzed by thymidylate kinase and pyrimidine nucleoside diphosphate kinase, respectively. The last product inhibits HIV-1 replication by interrupting the viral DNA chain elongation [7]. Low levels of TK activity could therefore induce a decrease in the amount of AZT-MP available for AZT-TP synthesis, thus reducing the therapeutic efficacy of AZT.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Inhibition of the salvage pathway by AZT is thus more devastating in U-937 cells and results in slowed growth or death of cells. Other investigators have demonstrated an initial decrease in TTP pools in a variety of cultured cells upon treatment with AZT [11][12][13]. Fridland, et.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work by Furman et. al., [11], has shown AZTMP is a competitive inhibitor of human thymidylate kinase (Ki = 8.6 μM). However, the highest concentrations of AZTMP were observed in H9c2 cells in which TMP was not observed.…”
Section: Effect Of Azt On Thymidine Phosphorylationmentioning
confidence: 99%